THE IMPACT OF LIQUEFIED PETROLEUM GAS CONVERSION ON WOMEN’S ACTIVITY - Fadhila Maulida (Journal of Applied Economics in Developing Countries, 2025)
This study examines the impact of Liquefied Petroleum Gas (LPG) conversion on women's empowerment indicated by married women's economic and social activity. LPG conversion is the biggest program for switching kerosene to LPG in Indonesia. This study uses work hours as a proxy for economic activity and the number of social gatherings as a proxy for social activity. The difference-in-difference method was used as the research method. The 4th and 5th wave data from the Indonesian Family Life Survey (IFLS) were used as the research data. The examination of married women was conducted in the analysis unit. Estimation of regional and demographic sub-samples was also performed to determine which received greater impact. Based on the estimation results, it is found that the LPG conversion can increase the work hours of average women by 209.64 hours/year or 4.03 hours/week and the number of social gatherings by 0.14. The sub-sample estimation also confirms that the impact of LPG conversion still has a positive causal effect on the two variables of interest. This paper adds to the existing literature by using the more comprehensive causal effect of using clean energy on women's empowerment, being the first study to analyze the impact of the LPG conversion program on women’s economic and social activity.